The Analysis Of Factors Affecting The High Level Of Pharmacy Turnover Of Pharmaceutical Installations In "Karangploso" Hospital Malang Regency - Sony Wiraganda (Journal for Quality in Public Health, 2020)
Pharmacy personnel include pharmacists and pharmacy technicians who are important HR in hospitals. The assessment was carried out based on an increase in the percentage of entry and exit or turnover of pharmacy staff at the "X" Hospital in 2017 by 33% (9 employees 3 who left), in 2018 by 55% (5 of 9 employees) and in 2019 by 45.4% (5 out of 11 employees leaving), "X" Hospital is a type C hospital located in Karangploso that serves general and specialist cases. the high turnover has an impact on organizations and individuals in organizations in the financial sector resulting in increased recruitment and training costs in the non-financial sector causing damage to social structure in the organization and a decrease in service quality, the purpose of this study is to determine the factors and causes of high employee turnover rates in pharmaceutical research plants in do qualitatively with approaches to three primary informants and 13 secondary informants. Data collection is done by interviews, observations and studies of research documents conducted in the outpatient pharmacy installation room (IFRJ) inpatient pharmaceutical installation (IFRI) and the Drug Warehouse Unit (UGO). It was found that what caused the turnover were: high workload, lack of energy, non-transparent distribution of incentives, lack of appreciation, dualism of leadership, and low organizational commitment. while the most influential factor being the main cause of turnover is the lack of appreciation and high workload. Advice hospital should make technological application breakthroughs to reduce workloads